2000
DOI: 10.1163/18759866-0690102010
|View full text |Cite
|
Sign up to set email alerts
|

Utility of 18S rDNA and ITS sequences as population markers for Lepeophtheirus salmonis (Copepoda: Caligidae) parasitising Atlantic salmon (Salmo salar) in Scotland

Abstract: Genetic differentiation within the salmon louse Lepeophtheirus salmonis (Krøyer, 1837), was investigated by the sequencing of specific nucleotide regions. Partial sequences of the 18S ribosomal RNA gene and the ribosomal internal transcribed spacer (ITS-1) region from single sea lice were amplified by the polymerase chain reaction (PCR). Lice were collected from wild and farmed Atlantic salmon (Salmo salar L., 1758) from nine selected localities around the Scottish coastline. A 0.9kb fragment of the 18S riboso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The compared sequences contained both relatively evolutionarily conserved (fragments of 18S and 28S rDNA and the complete 5.8S rDNA) and evolutionary variable genomic regions (ITS1 and ITS2). For different taxa, the ITS1 and ITS2 sequences vary significantly among individuals at the inter- and intrapopulation levels; furthermore, these sequences can exhibit intragenomic variability [ 25 , 41 , 53 , 54 ]. Recently, a high level of intrapopulation polymorphism of the 28S rDNA sequences was observed within Oithona spp.…”
Section: Resultsmentioning
confidence: 99%
“…The compared sequences contained both relatively evolutionarily conserved (fragments of 18S and 28S rDNA and the complete 5.8S rDNA) and evolutionary variable genomic regions (ITS1 and ITS2). For different taxa, the ITS1 and ITS2 sequences vary significantly among individuals at the inter- and intrapopulation levels; furthermore, these sequences can exhibit intragenomic variability [ 25 , 41 , 53 , 54 ]. Recently, a high level of intrapopulation polymorphism of the 28S rDNA sequences was observed within Oithona spp.…”
Section: Resultsmentioning
confidence: 99%
“…The varying degree of differentiation evident from RAPD analyses is potentially an artefact of insensitivity to detect small changes in the L. salmonis populations under study and difficulties in reproducibility. Shinn et al (2000) used L. salmonis from nine localities around the Scottish coastline from both farmed and wild salmonid hosts, and found greater similarity of L. salmonis ITS-1 sequences within farms than for the wild population sources.…”
Section: Introductionmentioning
confidence: 99%
“…For the salmon louse, L. salmonis , a close relative of C. elongatus , nucleotide sequence (Shinn, Banks, Tange, Bron, Sommerville, Aoki & Wootten 2000; Tjensvoll, Glover & Nylund 2006) and microsatellite (Nolan, Martin, Kelly, Glennon, Palmer, Smith, McCormack & Powell 2000; Todd, Walker, Ritchie, Graves & Walker 2004) analyses have demonstrated that the Atlantic salmon lice comprise a large population with no apparent clusters based on geographical locality. High dispersal of the parasites between geographically distant salmon louse populations causes a considerable genetic exchange and limits the divergence into distinct genetic variants.…”
Section: Discussionmentioning
confidence: 99%